Comparison of the keyhole trans-middle temporal gyrus approach and transsylvian approach for selective amygdalohippocampectomy: A single-center experience. (November 2020) - Uda, Hiroshi; Uda, Takehiro; Tanoue, Yuta; Koh, Saya; Kawashima, Toshiyuki; Nakajo, Kosuke; Ohata, Kenji; Goto, Takeo
Highlights: We compared transcortical and transsylvian selective amygdalohippocampectomy by single surgeon. The operation time and skin incision were shorter in TC SAH than in TS SAH. Visual-field defect, memory function, and seizure outcome were comparable. TC SAH may be superior in terms of shorter operation time and shorter skin incision. Abstract: Several approach routes exist for selective amygdalohippocampectomy (SAH); however, previous reports regarding a comparison of these routes are limited. Here, we compared trans-middle temporal gyrus (T2) SAH and transsylvian (TS) SAH in terms of seizure outcome, visual-field defect, memory function, and operation time in our institution. This retrospective study examined the data of 16 patients with medically intractable mesial temporal lobe epilepsy. Six patients underwent trans-T2 SAH and 10 patients underwent TS SAH between July 2014 and February 2019 in Osaka City University Hospital. In trans-T2 SAH, we performed a keyhole temporal craniotomy and a small corticotomy on T2. In TS SAH, we performed a 1.5 cm corticotomy along the inferior periinsular sulcus after opening the sylvian fissure. Amygdalohippocampectomy after reaching the inferior horn of the lateral ventricle was performed in the same manner in both procedures. The seizure outcome, visual-field defect, memory function, and operation time were retrospectively compared between the procedures. Seizure-free outcomes were achieved for six patients in the trans-T2 SAH and eight patients in the TS SAH group. There were no significant differences in the seizure outcome, visual-field defect, and memory function. The operation time was significantly shorter for trans-T2 SAH than TS SAH. The postoperative scar was less conspicuous for trans-T2 SAH. Trans-T2 SAH and TS SAH were comparable in terms of the seizure outcome, visual-field defect, and memory function. The operation time and length of the skin incision were shorter for trans-T2 SAH, suggesting that it may be preferable for general epilepsy surgeons.